Sosialisasi Manfaat Membuang Sampah pada Tempatnya bagi Siswa SD Abulyatama - Wiki Noviandi; Agusmadi Agusmadi; Azlim Azlim; Marah Sutan Rangkuti (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This community service aims to increase the awareness of Abulyatama Elementary School (SD) students regarding the importance of disposing of waste in its place and sustainable economic management. This socialization is expected to form positive habits in students and reduce waste problems in the environment around the school. Through educational activities involving students, teachers, and parents, this program aims to create a clean, healthy environment, and understand how waste management is related to economic management. The approaches used in this socialization are lectures, interactive discussions, and direct demonstrations regarding good waste management, as well as an introduction to the basic concepts of economic management.